Nitrate Removal from Drinking Water by Using Commercial Nanofiltration - Torabian, A.; Shokouhi Har, M.; R. Nabi Bidhendi, Gh.; Ghadimkhani, A. (Asian Journal of Chemistry, 2010)
The aim of the present work was to investigate the efficiency of commercial nanofiltration: NF90 (Dow-Film Tec) in reducing nitrate concentration from water. Salt rejection was studied using KNO3, NaNO3 and K2SO4. The influence of the operating pressure, feed concentration and temperature were studied. The influence of sulfate on the retention of KNO3 salt was also examined. To examine the influence of the nature of associated cation on nitrate retention, the retentions of two nitrate salts, KNO3 and NaNO3 were compared. The experiment results show that nitrate retention increases sharply by increasing the pressure from 4 to 8 bars and becomes stable at higher pressures but decreases by increasing temperature and also by increase in sulfate ion and nitrate salts concentrations. The retention of KNO3 was always lower than that of NaNO3.